EFEKTIVITAS SOSIALISASI PROGRAM ANTREAN ONLINE FKTP BPJS KESEHATAN MELALUI KANAL MEDIA SOSIAL - Anis Endang; Susri Adeni; Mahyudin Agung Harahap (SOURCE : Jurnal Ilmu Komunikasi, 2023)
This research was conducted to examine the effectiveness of the socialization of the First Level Health Facility (FKTP) online queuing program, which was carried out through the BPJS Kesehatan social media channel. Even though outreach has been carried out on social media channels that are close to the community, complaints about long queues at the FKTP are still often heard. This research was conducted using the snowball technique and distributing questionnaires online to 115 respondents. From the results of the survey conducted, it was found that more than half of the respondents did not have the mobile JKN application and were not aware of the online queue feature at FKTPs. However, most of the respondents stated that they had never experienced any problems when seeking treatment at the FKTP. The socialization carried out by BPJS Kesehatan is considered ineffective, as evidenced by the low number of application downloads compared to the number of JKN-KIS participants. In the writer's opinion, socialization efforts on BPJS Kesehatan social media channels and public figures partnered with BPJS Kesehatan with 500K followers on Instagram have not been able to provide socialization to the public in a broad reach and coverage.